EFFECT OF ADJACENT SHADING ON BUILDING ENVELOPE HEAT GAIN IN TROPICAL CLIMATE - Yaik-Wah Lim; Najib T. Al-Ashwal; David B. Dalumo; Pau Chung Leng (MATTER: International Journal of Science and Technology, 2025)
In tropical regions, approximately 60% of building energy is consumed by cooling systems, with heat gain through the building envelope being a major contributor. The Overall Thermal Transfer Value (OTTV) is a metric used to quantify average heat gain in air-conditioned buildings. However, the standard OTTV calculation does not account for shading from adjacent buildings—an increasingly common feature in high-density urban areas. This paper presents an empirical study on the thermal performance of building envelopes considering adjacent shading in tropical climates. Dynamic simulations of annual heat gain were conducted for buildings with and without adjacent shading for comparative analysis. The results highlight the significant impact of adjacent structures on heat gain performance and offer supplementary data to improve the current OTTV calculation method, especially for multi-block developments.